Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, \(\frac{8}{2^n}=2\Rightarrow2.2^n=8\)
\(\Rightarrow2^{n+1}=2^3\)
\(\Rightarrow n+1=3\)
\(\Rightarrow n=2\)
d,\(\left(2n-3\right)^2=9\)
\(\left(2n-3\right)^2=3^2\)
\(\Rightarrow\orbr{\begin{cases}2n-3=-3\\2n-3=3\end{cases}\Rightarrow\orbr{\begin{cases}2n=-3+3\\2n=3+3\end{cases}\Rightarrow}\orbr{\begin{cases}2n=0\\2n=6\end{cases}\Rightarrow}\orbr{\begin{cases}n=0\\n=3\end{cases}}}\)
Vậy n=0; n= 3
thay x=-1 ta có : \(\left(-x^2\right)+\left(-x^4\right)+\left(-x^6\right)+\left(-x^8\right)+....+\left(-x^{100}\right)\) =\(\left(-1^2\right)+\left(-1^4\right)+\left(-1^6\right)+\left(-1^8\right)+...+\left(-1^{100}\right)\) =1+1+1+1+...+1 = 50
\(\left(\frac{2}{5}\right)^2+5\frac{1}{2}:\left(4,5-2\right)-0,2\)
\(=\frac{4}{25}+\frac{11}{2}:\frac{5}{2}-\frac{1}{5}\)
\(=\frac{4}{25}+\frac{11}{2}.\frac{2}{5}-\frac{1}{5}\)
\(=\frac{4}{25}+\frac{11}{5}-\frac{1}{5}\)
\(=\frac{4}{25}+\frac{55}{25}-\frac{5}{25}\)
\(=\frac{54}{25}\)
a) Đề sai
b) \(\left|x+\frac{4}{5}\right|=\frac{1}{7}\)
\(\Rightarrow\orbr{\begin{cases}x+\frac{4}{5}=\frac{1}{7}\\x+\frac{4}{5}=\frac{-1}{7}\end{cases}}\Rightarrow\orbr{\begin{cases}x=\frac{1}{7}-\frac{4}{5}\\x=\frac{-1}{7}-\frac{4}{5}\end{cases}\Rightarrow\orbr{\begin{cases}x=\frac{5}{35}-\frac{28}{35}\\x=\frac{-5}{35}-\frac{28}{35}\end{cases}\Rightarrow}\orbr{\begin{cases}x=\frac{-23}{35}\\x=\frac{-33}{35}\end{cases}}}\)
Vậy \(x=\frac{-23}{35}\)hoặc \(x=\frac{-33}{35}\)
a)\(\left(\frac{1}{5}\right)^{10}.5^{20}=\left(\frac{1}{5}\right)^{10}.5^{10.2}=\left(\frac{1}{5}\right)^{10}.25^{10}=\left(\frac{1}{5}.5\right)^{10}=1^{10}=1\)
b)\(5^2.3^5.\left(\frac{3}{5}\right)^2=\left(\frac{3}{5}.5\right)^2.3^5=3^2.3^5=3^7\)
c)\(\left(\frac{1}{16}\right)^3:\left(\frac{1}{8}\right)^2=\left(\frac{1}{8}\right)^{2.3}:\left(\frac{1}{8}\right)^2=\left(\frac{1}{8}\right)^{6+2}=\left(\frac{1}{8}\right)^8\)
\(a.\left(\frac{1}{5}\right)^{10}.5^{20}=\left(\frac{1}{5}\right)^{10}.5^{10.2}=\left(\frac{1}{5}\right)^{10}.\left(5^2\right)^{10}=\left(\frac{1}{5}\right)^{10}.25^{10}=\left(\frac{1}{5}.25\right)^{10}=5^{10}.\)
\(b.5^2.3^5.\left(\frac{3}{5}\right)^2=\left[5^2.\left(\frac{3}{5}\right)^2\right].3^5=\left(5.\frac{3}{5}\right)^2.3^5=3^2.3^5=3^7\)\(c.\left(\frac{1}{16}\right)^3:\left(\frac{1}{8}\right)^2=\left[\left(\frac{1}{4}\right)^2\right]^3:\left[\left(\frac{1}{2}\right)^3\right]^2=\left(\frac{1}{4}\right)^6:\left(\frac{1}{2}\right)^6=\left(\frac{1}{4}:\frac{1}{2}\right)^6=\left(\frac{1}{2}\right)^6\)
\(A=1+2+2^2+...+2^{2017}\)
\(\Rightarrow A=\dfrac{2^{2017+1}-1}{2-1}\)
\(\Rightarrow A=2^{2018}-1\)
mà \(B=2^{2018}\)
\(\Rightarrow A-B=2^{2018}-1-2^{2018}\)
\(\Rightarrow A-B=-1\)
\(2A=2+2^2+2^3+...+2^{2018}\)
\(\Rightarrow A=2A-A=2^{2018}-1\)
\(\Rightarrow A-B=2^{2018}-1-2^{2018}=-1\)
Lời giải:
\(A=2^{2016}-(2^{2015}+2^{2014}+...+2^2+2)\)
\(\Rightarrow 2A=2^{2017}-(2^{2016}+2^{2015}+....+2^3+2^2)\)
\(\Rightarrow 2A-A=[2^{2017}-(2^{2016}+2^{2015}+...+2^3+2^2)]-[2^{2016}-(2^{2015}+2^{2014}+...+2^2+2)]\)
\(A=2^{2017}-2^{2016}-2^{2016}+2\)
\(=2^{2017}-2.2^{2016}+2=2^{2017}-2^{2017}+2=2\)